Optimizing percutaneous pulmonary valve implantation with patient-specific 3D-printed pulmonary artery models and hemodynamic assessment - Odemis, Ender; AKA, İbrahim Basar and Ali, Mhd Homam Alhaj and Gumus, Terman and Pekkan, Kerem (Frontiers in Cardiovascular Medicine, 2024)
Background: Percutaneous pulmonary valve implantation (PPVI) has emerged as less invasive alternative for treating severe pulmonary regurgitation after Tetralogy of Fallot (TOF) repair in patients with a native right ventricular outflow tract (RVOTs). However, the success of PPVI depends on precise patient-specific valve sizing, the avoidance of oversizing complications, and optimal valve performance. In recent years, innovative adaptations of commercially available cardiovascular mock loops have been used to test conduits in the pulmonary position. These models are instrumental in facilitating accurate pulmonic valve sizing, mitigating the risk of oversizing, and providing insight into the valve performance before implantation. This study explored the utilization of custom-modified mock loops to implant patient-specific 3D-printed pulmonary artery geometries, thereby advancing PPVI planning and execution. Material and Methods: Patient-specific 3D-printed pulmonary artery geometries of five patients who underwent PPVI using Pulsta transcatheter heart valve (THV) ® were tested in a modified ViVitro pulse duplicator system®. Various valve sizes were subjected to 10 cycles of testing at different cardiac output levels. The transpulmonary systolic and regurgitation fractions of the valves were also recorded and compared. Results: A total of 39 experiments were conducted using five different patient geometries and several different valve sizes (26, 28, 30, and 32 mm) at 3, 4, and 5 L/min cardiac output at heart rates of 70 beats per minute (bpm) and 60/40 systolic/diastolic ratios. The pressure gradients and regurgitation fractions of the tested valve sizes in the models were found to be similar to the pressure gradients and regurgitation fractions of valves used in real procedures. However, in two patients, different valve sizes showed better hemodynamic values than the actual implanted valves. Discussion: The use of 3D printing technology, electromagnetic flow meters, and the custom modified ViVitro pulse duplicator system® in conjunction with patient-specific pulmonary artery models has enabled a comprehensive assessment of percutaneous pulmonic valve implantation performance. This approach allows for accurate valve sizing, minimization of oversizing risks, and valuable insights into hemodynamic behavior before implantation. The data obtained from this experimental setup will contribute to advancing PPVI procedures and offer potential benefits in improving patient outcomes and safety.